Art and contemporaneity - Ruda, Frank; Voelker, Jan (Diaphanes, 2015)
Art is often said to be timeless, but specific works of art always take place within time and maintain a dynamic balance between their conditions of production and reception. Art and Contemporaneity features contributions from leading scholars, including Alain Badiou and Alexander García Düttmann, who bring theories of aesthetic philosophy to bear on one of the most crucial questions about contemporary art: how do works of art come to exist within and in relation to time? A specific temporality of an artwork emerges from the material and political conditions of its production. But wo.